Historical dictionary of African-American television - Fearn-Banks, Kathleen (Historical dictionaries of literature and the arts, 2006)
Lists African-American actors and performers with starring, regular, or key roles in television series, made-for-television movies, and miniseries; also lists key productions with African-American casts or African-American themes in all genres, including sports, documentaries, and other broadcasts. African-American news and sports anchors and reporters on network broadcasts are also listed. Covers national television through its early days up to 2005.